ANALISIS KEBERHASILAN IMPLEMENTASI DIGITALISASI SISTEM ADMINISTRASI PERPAJAKAN DI INDONESIA - Devi Nur Cahaya Ningsih; Dewi Noor Fatikhah Rokhimakhumullah; Estu Unggul Drajat; Krisna Ganda Saputra; Anjani Bunga Irawan (Bajang Institute, 2024)
Diigitalization has the meaning of a series of transitions from previously using print, video and audio media to digital forms. Likewise, tax administration is not spared from the digitization process, such as the application of e-registration, e-billing, e-faktur, e-SPT and e-bupot. The purpose of this study is to determine the success of digitizing tax administration in the application of e-documents in Indonesia. The method used in this study is a qualitative method by conducting in-depth interviews and direct observation to the DGT Sub Directorate of Potential, Compliance and Acceptance; and the Fiscal Policy Agency. Meanwhile, reports from this study will be written using a descriptive method. To analyze the success of digitizing tax administration in Indonesia, several theories are used including the IS Success Model, Institutional Theory and Based on IS Success Literature Review. The results of this study indicate that the implementation of tax digitization can be said to be successful from a technological aspect with indicators of information quality, system quality, service quality, accessibility, and perceived ease of use. But on the other hand, digitization of taxation cannot be said to be successful when viewed from a contextual aspect with indicators of socio-demographic characteristics, digital divide, and technological trends around the world